2003
DOI: 10.1161/01.cir.0000070591.21548.69
|View full text |Cite
|
Sign up to set email alerts
|

Human Aortic Valve Calcification Is Associated With an Osteoblast Phenotype

Abstract: Background-Calcific aortic stenosis is the third most common cardiovascular disease in the United States. We hypothesized that the mechanism for aortic valve calcification is similar to skeletal bone formation and that this process is mediated by an osteoblast-like phenotype. Methods and Results-To test this hypothesis, we examined calcified human aortic valves replaced at surgery (nϭ22) and normal human valves (nϭ20) removed at time of cardiac transplantation. Contact microradiography and microcomputerized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
476
1
15

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 636 publications
(506 citation statements)
references
References 15 publications
(14 reference statements)
10
476
1
15
Order By: Relevance
“…RANK is expressed in normal valve leaflets, but is downregulated in aortic valve lesions. 65 The osteoblast-specific transcription factor, Runx2/Cbfa1, has been detected in rabbit models of experimental aortic valve disease, 16,17,27 and osteoblast-like cells have been identified both in a rabbit model 17 and in calcified human valves. 15 Finally, a subset of end-stage human aortic valve lesions contain heterotopic bone, 15 further confirming the dysregulated nature of aortic valvular calcification.…”
Section: Calcificationmentioning
confidence: 99%
See 2 more Smart Citations
“…RANK is expressed in normal valve leaflets, but is downregulated in aortic valve lesions. 65 The osteoblast-specific transcription factor, Runx2/Cbfa1, has been detected in rabbit models of experimental aortic valve disease, 16,17,27 and osteoblast-like cells have been identified both in a rabbit model 17 and in calcified human valves. 15 Finally, a subset of end-stage human aortic valve lesions contain heterotopic bone, 15 further confirming the dysregulated nature of aortic valvular calcification.…”
Section: Calcificationmentioning
confidence: 99%
“…The first was the long-held notion that calcific aortic valve disease was a "degenerative," and therefore unmodifiable, condition. 6 However, more recent studies have demonstrated convincingly that calcific aortic valve lesions have many features characteristic of an active pathobiological process, including chronic inflammation, [7][8][9] lipoprotein deposition, 10 -12 active calcification, [13][14][15][16][17][18] and renin-angiotensin system activation. 19,20 These features are present in both trileaflet and bileaflet aortic valve lesions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…В экспериментах in vivo было показано, что в стенотически измененных клапанах фибробласты приобретают свойства плюрипотент-ных клеток, способных к остеобластической диффе- ренцировке. "Активированные" фибробласты (или миофибробласты) имеют сходные свойства с остео-бластами костной ткани и обладают возможностью синтезировать остеогенные медиаторы [7]. Наиболее изученными регуляторными путями экспрессии остеогенных медиаторов "активирован-ными фибробластами" являются: пути трансформи-рующих факторов роста (TGFβ1 и β3), в том числе костных морфогенетических белков (bone morphogenetic protein -BMP), Wnt, RANK/RANKL и Notch1 пути.…”
Section: молекулярно-генетические факторы ассоциированные с развитиеunclassified
“…Over the last ten years, the scientific progress in the field of calcific AS progression has been substantial 6,7 . Historically, calcific AS has been associated with passive, age-related valve degeneration.…”
Section: Pathology Of Calcifi C Aortic Stenosismentioning
confidence: 99%